Critical thinking : a student's introduction - Gregory Bassham; William Irwin; Henny Nardone; James M. Wallace; King's College (New York : McGraw-Hill Education, 2019)
In a hyper-connected digital world buzzing with both information and illogic, facts and spin, critical thinking has never been more challenging or important. This popular, learner-friendly text gives today's students the critical reasoning tools they need to survive and thrive--in school, in their careers, and in life. It covers all the basics of critical thinking, using class-tested real-world examples and a proven step-by-step approach. Its comprehensiveness allows instructors to tailor the material to their individual teaching styles, resulting in an exceptionally versatile text.
Keywords: Critical thinking; Textbooks